2009
DOI: 10.2116/analsci.25.1095
|View full text |Cite
|
Sign up to set email alerts
|

Noncompetitive Immunodetection of Benzaldehyde by Open Sandwich ELISA

Abstract: Benzaldehyde (Bz) is a typical fragrant compound for peach-flavored beverages. In the food and beverage industries there is great demand for a sensitive and easy detection system of Bz in order to ensure product quality control and to avoid contamination. For the noncompetitive detection of Bz, we applied an open-sandwich enzyme-linked immunosorbent assay (OS-ELISA) utilizing an antigen-dependent reassociation of antibody variable region fragments, VH and VL. We cloned the VH and VL genes of an anti-Bz monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Compared with different biosensors for benzadehyde detection, such as immunosensor, enzyme sensor and cell-based sensor (Badalyan et al , 2014; Gobi et al , 2007; Badalyan et al , 2013; Fiorentino et al , 2009; Shirasu et al , 2009), the OBPs-based biosensor showed relatively broad detection ranges. It suggested that the biosensor showed a relatively high sensitivity to benzaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with different biosensors for benzadehyde detection, such as immunosensor, enzyme sensor and cell-based sensor (Badalyan et al , 2014; Gobi et al , 2007; Badalyan et al , 2013; Fiorentino et al , 2009; Shirasu et al , 2009), the OBPs-based biosensor showed relatively broad detection ranges. It suggested that the biosensor showed a relatively high sensitivity to benzaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…We can obtain antibodies against these fragrant compounds through the iliac lymph node method. Anti-fragrant monoclonal antibodies were developed [ 73 ], and an SPR measurement and open-sandwich enzyme-linked immunosorbent assay for benzaldehyde were carried out [ 74 , 75 ].…”
Section: Clues For Improvement Of Electronic Dog Nosementioning
confidence: 99%
“…Up to now, the OSIA system has been successfully applied in the detection of hapten molecules such as gibberellin (Lee et al, 2008), benzaldehyde (Shirasu et al, 2009), zearalenone (Suzuki et al, 2007), 4-hydroxy-3-nitrophenylacetyl (Yokozeki et al 2002), the carboxylterminal peptide of human osteocalcin (BGP) (Lim et al 2007), bisphenol A (Sakata et al 2009), and 11-Deoxycortisol ). This novel immunoassay system could be done in a shorter period of time than using a conventional sandwich assay, due to the omission of an incubation/washing cycle.…”
Section: Open Sandwich Immunoassay (Osia)mentioning
confidence: 99%